Comparing Supplementary Ethnic Schools and the Academic Achievement of Chinese Immigrant Students in Quebec and Flanders - Sun, Ming; Braeye, Sarah (Diversité urbaine, 2012)
Supplementary or extra-curricular ethnic schools have been neglected in the research literature, especially in non-English speaking contexts such as Quebec and Flanders. Yet they are important for understanding the influence of ethnic social structures on the educational integration and academic achievement of immigrant students. From a comparative perspective, this paper focuses on the response of Chinese language schools to the educational needs of Chinese youth. Data were collected through ethnographic observations in Chinese schools in Quebec and Flanders,1 as well as in semi-structured interviews with students of Chinese origin, their parents, and school personnel. The findings demonstrate that the influence of ethnic social structures on the progression of minority/immigrant students through schooling is related to the particular profile of their ethnic community, as well as to the larger socio-economic and political environment of the host society.